11(p-3)=2y+2

Simple and best practice solution for 11(p-3)=2y+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(p-3)=2y+2 equation:


Simplifying
11(p + -3) = 2y + 2

Reorder the terms:
11(-3 + p) = 2y + 2
(-3 * 11 + p * 11) = 2y + 2
(-33 + 11p) = 2y + 2

Reorder the terms:
-33 + 11p = 2 + 2y

Solving
-33 + 11p = 2 + 2y

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '33' to each side of the equation.
-33 + 33 + 11p = 2 + 33 + 2y

Combine like terms: -33 + 33 = 0
0 + 11p = 2 + 33 + 2y
11p = 2 + 33 + 2y

Combine like terms: 2 + 33 = 35
11p = 35 + 2y

Divide each side by '11'.
p = 3.181818182 + 0.1818181818y

Simplifying
p = 3.181818182 + 0.1818181818y

See similar equations:

| 5x-2=4x+11 | | 0.3(2x-3)=0.7(8-x) | | 5c+7=95-6c | | 5x-69=7x+21 | | 1/2x-9=x-3 | | .25x-y=3 | | 2x+10=5x-80 | | 12x-25=8x+23 | | -5x/2=-1 | | 4x-5y=-32 | | 10x+20x=150 | | 4x-5y=-32graph | | 3x/2=-3 | | 8x+5-4x=-20 | | x-1=x^2-6x+9 | | -1x/3=-12 | | 4t+16-6= | | x/5+7=27 | | 5x^2-40x-10=0 | | 1x/3=0 | | 5x^2+40x-10=0 | | f=200+25+.02x | | x^2-20x-76=-7 | | 6x-5x+3/4=-1/12 | | 10x-24=2x-56 | | 14x+8/2=39 | | x^2+10x-14=10 | | a/12=8 | | x^2-6x-17=10 | | 4=-2/-5 | | 1x^2+3x-24=0 | | 0.3(x+50)+0.7x=40 |

Equations solver categories